(untitled) - K.Naresh Kumar, Y.Alexander Jeevanantham, K.Kaliagurumoorthi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper presents a new converter transformer with Active Compensator (LS - UPQC) to provide shunt and series compensation in the power system networkin order to eliminate the power quality problems. The power network delivers power supply to dissimilarclassesof loads like rectifier fed motor drives, uninterruptible power supplies etc. NCT embraces an unmistakable wiring game plan at the optional side joining two windings in particular as auxiliary broadened winding and auxiliary basic winding. In the middle of these two winding an interfacing point is accessible to associate the remunerating gadgets. The shunt and arrangement dynamic channel together called as LS - UPQC are associated at the association highlight decrease the current and voltage quality and to keep up the sinusoidal conduct of the approaching force supply to the heap at the force framework organization. Introduction of NCT with LS - UPQC is a lot of successful when identified with bygone shunt dynamic force sifting (SAPF) technique.